2010
DOI: 10.1007/s11548-010-0407-x
|View full text |Cite
|
Sign up to set email alerts
|

Computer assisted determination of acetabular cup orientation using 2D–3D image registration

Abstract: Our new solution formulation and the hybrid 2D-3D registration scheme facilitate estimation of post-operative cup orientation and measurement of pelvic tilt and rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The placement of the cup may be in the safe zone by one definition but outside the safe zone by other definitions. It is therefore important to use the same reference plane (APP or coronal plane) when comparing component position after THA [24,25,27]. In this study, we found a good accuracy of the radiographic vector arithmetic cup measurement technique with a mean of under 2°for inclination and under 1°for anteversion when compared to a 3D-CT reconstruction model within the coronal plane.…”
Section: Tab 2 Messergebnisse Für Inklination Und Anteversion Im Ap mentioning
confidence: 58%
See 1 more Smart Citation
“…The placement of the cup may be in the safe zone by one definition but outside the safe zone by other definitions. It is therefore important to use the same reference plane (APP or coronal plane) when comparing component position after THA [24,25,27]. In this study, we found a good accuracy of the radiographic vector arithmetic cup measurement technique with a mean of under 2°for inclination and under 1°for anteversion when compared to a 3D-CT reconstruction model within the coronal plane.…”
Section: Tab 2 Messergebnisse Für Inklination Und Anteversion Im Ap mentioning
confidence: 58%
“…Widmer reported a protractor for measuring the anteversion of acetabular cups on radiographs, but with limited precision and a substantial error range from −16.6°to 29.8° [ 6]. Other studies reported that errors in measuring the cup position with various radiographic measurement methods could be high, exceeding 20 degrees, due to the wide variability in individual pelvic orientation relative to the radiographic film plate during image acquisition [6,7,24,25]. Similarly, estimating dynamic pelvic tilt intraoperatively is challenging.…”
Section: Tab 2 Messergebnisse Für Inklination Und Anteversion Im Ap mentioning
confidence: 99%
“…In many clinical applications, e.g. image‐free navigation for total hip arthroplasty (THA) , antero‐posterior (AP) pelvic radiographs are the sole imaging data available for preoperative planning and postoperative assessment .…”
Section: Introductionmentioning
confidence: 99%
“…Under this context, Zheng introduced a method to reconstruct a patient‐specific three‐dimensional (3D) surface model of the pelvis from a single two‐dimensional (2D) AP pelvic radiograph. A patient‐specific 3D pelvis model like those generated from other imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI) can be used by surgeons to plan an intervention of THA, and determine the acetabular cup orientations after THA . A patient‐specific 3D model of the hip joint is helpful for understanding and simulating patient's joint mechanics such as range of motion (ROM) , postoperatively evaluating the implanted stem and head of THA , quantitatively analyzing hip osteoarthritis (OA) , or morphologically assessing femoroacetabular impingements (FAI) .…”
Section: Introductionmentioning
confidence: 99%
“…Image registration of computed tomography (CT) or MRI can be used to determine joint transformations (Crisco et al 2001;Rogers et al 2002;Gardner et al 2006;Tay et al 2008;Zheng and Zhang 2010;Svedmark et al 2012). Surface registration is often used, but voxel-based image registration has been shown to have a similar/better accuracy [mean translation error of 0.21 mm and rotation error of 1.298 compared with mean translation error of 0.8 mm and rotation error of 1.58 for CT-based surface registration (Moojen et al 2003;Goto et al 2005;Gardner et al 2006)].…”
Section: Introductionmentioning
confidence: 99%